Brazilian future land-use dynamics and impacts of deforestation policies - Ambrósio, Geanderson Eduardo (2019)
Land use interacts with a dichotomous relationship between agricultural production and forest conservation, it depends on socioeconomic and biophysical features, and it has time and geographic specific dynamics. National environmental policies can drive national land-use change (LUC) and, due to interconnected global markets, it affects international land dynamics in positive or negative ways. The present research uses a global land-use model to assess Brazilian land-use dynamics by projecting and evaluating i) Brazilian LUC over this century and ii) the national and international impacts of Brazilian deforestation policies over 2050. Results on LUC over this century suggest that Brazilian land use can evolve in diverse pathways depending on the socioeconomic and biophysical assumptions. Pastureland presents an important decrease in the next decades while cropland takes over it and keeps increasing up to 2040, especially in the South and Northeast. Deforestation and depletion of natural land fade out in the next decades and this dynamic can be due to the abandonment of pasturelands and to policies to reduce deforestation. If the world tracks the path to stay below the 2- degree warming, Brazil would benefit of the establishment of a biofuel market by producing and exporting bioenergy crops, but at the cost of increased food prices due to higher land competition. Results on the impacts of deforestation mitigation revealed that these policies have a major impact on reducing deforestation in Brazil. Mitigation policies for Legal Amazon and Cerrado present a net saving of up to 50 million ha of forestland from 1995 to 2050 and are associated with higher crop yields. This policy promotes agricultural reallocation to other countries, resulting in deforestation and Carbon emissions in these countries, but such effects are lower than the Brazilian mitigation. This counterbalancing demonstrates that Brazil’s mitigation results are higher than its effective contribution to global mitigation. By one side, the diverse land-use pathways to 2100 suggest that Brazil may still have time to drive its LUC according to its interests. However, as relative global results are lower than the individual Brazilian achievement, the time that Brazil may still have to act and drive its land use may also be used to design cooperative international policies in order to enhance global effectiveness.